Development and Validation of RP-HPLC Method for Quantitative Analysis of Sulfamethoxazole and Trimethoprim in Liquid Suspension: A Comparative Study with Compendial Method - Aslam, Muhammad; Ali, Shahzad; Ahmed, Mahmood; Aneeq Javed, Muhammad; Afsah Iftikhar; Abbas, Yousaf; Sohail, Aamir; Abdul-Rehman, Mehvish; Habibullah, Khansa (Scientific Inquiry and Review, 2023)
Co-trimoxazole is a combination of trimethoprim or sulfamethoxazole. It is used to treat common infectious diseases, including the lung disorders, urinary disorders, and gastrointestinal infections. The current study was performed to develop a new RP-HPLC technique. The main purpose was to analyze SMX (Sulfamethoxazole) and TMP (Trimethoprim) in a liquid medium of 60mL. The analyses of SMX and TMP were performed on RP-HPLC with a C18 column (25 cm × 4.6 mm) packed with 5 µm ODS, L1 stationary phase, while the mobile phase consisted of methanol and water with a ratio of 6:4. The pH of the system was adjusted to 2.6 by using dilute phosphoric acid. The injection volume was 20μL having a flow rate of 1 mL/minute and column temperature of 40ºC. The analysis of all chromatograms was performed at a single wavelength of 254 nm. The validation of the method was determined for range, precision, linearity, specificity, accuracy, and system suitability. This method was found to be more environmentally friendly with respect to the other compendial methods, which are used for the TMP and SMX analysis.